IDENTIFIKASI MINERAL SEKUNDER UNTUK MENILAI POTENSI TANAH LAHAN PERTANIAN CABE HIYUNG DI DESA HIYUNG KABUPATEN TAPIN KALIMANTAN SELATAN - Taher, Ratna; Syarbini, Muhammad (Universitas Lambung Mangkurat, 2024)
Hiyung Village is part of Tapin Tengah District, Tapin Regency, South Kalimantan. Besides rice, superior agricultural commodities in this village is Hiyung Cayenne Pepper. High demand and prices have caused more and more cayenne pepper to be cultivated. Hiyung Cayenne Pepper Cultivation is expected to increase farmers' income, so efforts are needed so that agricultural activities can continue. The sustainability of agricultural can be maintained if they are managed well. Appropriate management actions can be implemented if the soil and land characteristics are known. Soil is one of the things that really determines the success of an agricultural business, especially the availability of nutrients. Analysis of the secondary mineral composition of soil (sand) is very important in order to determine the nutrient reserves in the soil. Information about nutrient reserves in the soil can be used as a basis for good soil management so that it meets plant needs and does not cause damage to the soil and the environment. The specific aim of this research is to determine the composition of primary minerals (sand) to identify nutrient reserves in the soil. This research was carried out using a survey method to obtain data or information on soil and land characteristics and current management. Observations and soil sampling in the field were carried out at 5 locations with a distance of 1 km between locations. Sand mineral analysis uses a polarizing microscope to determine the mineral composition. Primary minerals (sand) at the research location are dominated by rock fragments and quartz. The weatherable mineral content is very small so the potential for nutrient reserves is very small.